2015
DOI: 10.5194/acp-15-8695-2015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2009 major sudden stratospheric warming on the composition of the stratosphere

Abstract: Abstract. In a case study of a remarkable major sudden stratospheric warming (SSW) during the boreal winter 2008/09, we investigate how transport and mixing triggered by this event affected the composition of the entire stratosphere in the Northern Hemisphere. We simulate this event with the Chemical Lagrangian Model of the Stratosphere (CLaMS), both with optimized mixing parameters and with no mixing, i.e. with transport occurring only along the Lagrangian trajectories. The results are investigated by using t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 76 publications
3
24
0
Order By: Relevance
“…In the current section, as an example, we assume PW 16 with m = 1 is the underlying mode of P 1 for discussing the interactions S2 ± P 1 = S2S1± as SW2 ± PW 16 = S1±. The existence of stratospheric PWs with m = 1 during the 2009 SSW were reported in meteorological analyses (e.g., Labitzke & Kunze, ; Matthias et al, ; Sassi et al, ) and satellite observations (Manney et al, ; Tao et al, ). Although a PW‐like structure with m = 2 was observed at the late stage of 2009 SSW (e.g., Labitzke & Kunze, ; Manney et al, ), according to our analysis the in situ m = 2 structure does not correspond to the frequency of P 1 or P 2 but P 3 in Figure , as we will discuss in an independent paper.…”
Section: Discussionmentioning
confidence: 89%
“…In the current section, as an example, we assume PW 16 with m = 1 is the underlying mode of P 1 for discussing the interactions S2 ± P 1 = S2S1± as SW2 ± PW 16 = S1±. The existence of stratospheric PWs with m = 1 during the 2009 SSW were reported in meteorological analyses (e.g., Labitzke & Kunze, ; Matthias et al, ; Sassi et al, ) and satellite observations (Manney et al, ; Tao et al, ). Although a PW‐like structure with m = 2 was observed at the late stage of 2009 SSW (e.g., Labitzke & Kunze, ; Manney et al, ), according to our analysis the in situ m = 2 structure does not correspond to the frequency of P 1 or P 2 but P 3 in Figure , as we will discuss in an independent paper.…”
Section: Discussionmentioning
confidence: 89%
“…To our knowledge, this connection between PJO-SSW events and persistent weak upwelling in the tropics had not been noticed before. It is oftentimes assumed that the BDC is stronger in winters with SSWs (Abalos et al, 2015;Tao et al, 2015). This may be the case close to the SSW onset, but there are anomalies of both signs before and after SSWs and the effect on seasonal estimates of the BDC is not straightforward.…”
Section: Isentropic Mixingmentioning
confidence: 99%
“…This series of papers also highlighted the intraevent variability in the response of the tracers, particularly when the activation of chemical reactions depends on meeting certain thresholds. Using the Chemical Lagrangian Model of the Stratosphere to study the SSW of January 2009, Tao et al () concluded that mixing across the weakened vortex edge accounted for a large fraction of the ozone changes in the polar stratosphere after the onset of the SSW.…”
Section: Introductionmentioning
confidence: 99%
“…Mesospheric responses to the SSW are observed as enhancement in planetary wave amplitude, zonal wind reversal, and significant air cooling (Shepherd et al, 2014;Zülicke and Becker, 2013;Stray et al, 2015;Zülicke et al, 2018); substantial depletion of the metal layers (Feng et al, 2017;Gardner, 2018); and mesosphere-to-stratosphere descent of trace species (Manney et al, 2009;Salmi et al, 2011). The SSW events are also accompanied by the rapid descent of the stratopause into the stratosphere at the SSW onset, followed by formation of the elevated stratopause in the lower mesosphere and gradual stratopause lowering toward its typical position in the SSW recovery phase (Manney et al, 2009;Chandran et al, 2011;Salmi et al, 2011;Tomikawa et al, 2012;Limpasuvan et al, 2016;Orsolini et al, 2010Orsolini et al, , 2017. The elevated stratopause events provide evidence for the coupling between the stratosphere and the mesosphere.…”
Section: Introductionmentioning
confidence: 99%